2020
DOI: 10.1101/2020.04.02.20048892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of viral epidemic outbreaks on mental health of healthcare workers: a rapid systematic review

Abstract: Objectives:To examine the impact of providing healthcare during or after health emergencies caused by viral epidemic outbreaks on healthcare workers´(HCWs) mental health, and to assess the available evidence base regarding interventions to reduce such impact.Design: Systematic rapid review and meta-analysis.Data sources: MEDLINE, Embase, and PsycINFO, searched up to 23 March 2020. Method:We selected observational and experimental studies examining the impact on mental health of epidemic outbreaks on HCWs. One … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
3
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 114 publications
8
80
3
11
Order By: Relevance
“…Existing work has focused on those individuals most directly affected by disease (e.g., infected individuals and their families, healthcare workers ( 1 5 ) and examined mental health impacts across broader communities only after the acute phase has passed ( 1 ). In the acute phase however, fear about potential exposure to infection, loss of employment, and financial strain are also likely to increase psychological distress in the broader population ( 1 4 ). This distress may be further exacerbated in individuals who have experienced prior traumatic events ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Existing work has focused on those individuals most directly affected by disease (e.g., infected individuals and their families, healthcare workers ( 1 5 ) and examined mental health impacts across broader communities only after the acute phase has passed ( 1 ). In the acute phase however, fear about potential exposure to infection, loss of employment, and financial strain are also likely to increase psychological distress in the broader population ( 1 4 ). This distress may be further exacerbated in individuals who have experienced prior traumatic events ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 43 This finding was reflected in another systematic review, which only found three studies that evaluated interventions to improve the resilience of clinicians working in a viral outbreak, one of which was in preparation for a potential influenza pandemic. 77 The third study in that review was the before and after evaluation of the effect of a SARS prevention programme on anxiety and depression during the outbreak in Taiwan that was included in our review. 35 Study quality was only fair, with 45 out of the 59 studies scoring 7 or higher on the Joanna Briggs Institute tool.…”
Section: Individual Factorsmentioning
confidence: 99%
“…They assessed a wide range of disturbing psychological reactions for their impact on the mental health of workers providing health care during or after health emergencies caused by viral epidemic outbreaks. Anxiety (45%) was the highest pooled prevalence, followed by depression (38%), acute stress disorder (31%), and post-traumatic stress disorder (19%), while the prevalence of burnout was 29% (in 1,168 participants), as reported by three studies (8).…”
Section: Introductionmentioning
confidence: 73%
“…This result is in line with the result of a rapid systematic review conducted by Ricci-Cabello and colleagues. They reported that the pool prevalence of depression among health care workers during a viral epidemic outbreak was 38% (8). Our study also aimed to analyze the complex associations between depression and burnout among the study population.…”
mentioning
confidence: 98%